Factors Limiting Accounting. - Littleton, A. C. (The Accounting Review, 1970)
The article provides information on the factors that limit the accounting process. When accounts are summarized in the form of financial statements, they compactly present figure-pictures of the economic results of transaction decisions affecting the enterprise concerned. The information service of accounting makes a unique contribution to the needs which interested parties have in order to understand the impact management's decisions have had on the enterprise involved. Clearly, account data, even when carefully summarized into financial statements, must be read analytically and with a clear awareness that those data only report on specific transaction experience previously consummated by that specific enterprise. In reading financial statement summaries of enterprise transaction experience, one should clearly realize that the reported amounts originated in prior transactions acceptably completed between independent parties free to trade or not to trade. Enterprise accounting can perform a socially useful service because its data are "pure," that is, faithful to the price-aspects of that enterprise's actual transaction events in the markets.